Inovasi Program Pembelajaran Berbasis Social Emotional Skills sebagai Penguat Pendidikan Karakter Madrasah - Ghofur, Abdul (MANAGIERE: Journal of Islamic Educational Management, 2023)
This research aims to describe learning development innovations in Islamic education institutions in the 21st century. The development of Islamic education institutions is something that must be done in order to realize people who are virtuous and intelligent as the values of Islamic teachings. With a qualitative method in the form of a case study, this research was conducted at MI NU Banat Kudus. Data collection techniques used include observation, interview, documentation, and triangulation techniques. Then, the data that has been collected is analyzed by data reduction, data presentation, and conclusion drawing and verification. The results showed that SES development innovation at MI NU Banat Kudus was implemented with two programs, namely the language environment program and lesson study. The language environment program aims to train students' language skills and abilities by scheduling four languages (English, Arabic, Indonesian, and Javanese) alternately every week. The lesson study program aims to develop a good practice of SES integration in learning, increasing the ability of teachers to observe learning activities, cultivating learning models based on inquiry, and increasing teacher professionalism.